Path analysis of sap flow of tomato under rain shelters in response to drought stress - Guangcheng, Shao; Doudou, Huang; Xi, Cheng; Jingtao, Cui; Zhenhua, Zhang (International Journal of Agricultural and Biological Engineering, 2016)
The physiological characters and growth of tomato (Solanum lycopersicum L.) were recorded to be largely affected by different levels of irrigation. The objectives of this research were to determine the effects of deficit irrigation and rain shelters on sap flow, relative water content and the relationship between sap flow and environmental parameters. Experiments under rain shelters conditions were conducted in southern China during the growing seasons in 2012. The threshold of irrigation was designed at 80% field capacity during the whole period (T1, the control), and 30%, 40% and 50% decreased water of T1 were applied as the treatments of T2, T3 and T4. The plants subjected to water stress exhibited a decrease in the values of sap flow rate and relative water content. Calculation of 95% confidence level revealed a significant difference of sap flow rate in T4 and T3 as well as the control on sunny and rainy days. The diurnal variation of the sap flow showed a single peak curve on sunny day, while it demonstrated irregular multi-peak variation on rainy days. The study also showed that the most sensitive environmental indicator affecting sap flow was solar radiation, followed by air temperature and vapour pressure deficit. Direct path coefficient was basically consistent with the coefficient of correlation, but there was slight difference between the total contribution R2 and that of variable factors. Keywords: drought stress, tomato, sap flow, rain shelters, deficit irrigation, path analysis DOI: 10.3965/j.ijabe.20160902.1405 Citation: Shao G C, Huang D D, Cheng X, Cui J T, Zhang Z H. Path analysis of sap flow of tomato under rain shelters in response to drought stress. Int J Agric & Biol Eng, 2016; 9(2): 54－62.